The securitization of memorial space : rhetoric and public memory - Paliewicz, Nicholas S.; Hasian, Marouf Arif, Jr (University of Nebraska Press, 2019)
"In The Securitization of Memorial Space, the authors contend that the National September 11 Memorial Museum is a securitized site of remembrance that evokes feelings of insecurity that justify post-9/11 policies and war"--